Statistical parameters to estimate the leaf area of native forest seedlings of genus Tabebuia and Handroanthus (Bioscience Journal, 2017)
Leaf area (LA) is an important parameter for physiological and phytotechnical studies and its measurement in a fast, accurate, and inexpensive way is essential and desirable. In this context, mathematical modeling is used as a tool to estimate leaf area from its relation with biometrical parameters and biomass. This study aimed to generate, validate, and determine the best mathematical estimation models of leaf area using the linear variables length (with and without petiole) and width of leaves and leaflets, in addition to dry mass of the native species Tabebuia roseoalba, Tabebuia impetiginosa and Handroanthus chrysotrichus collected in Sinop, Mato Grosso State (Brazil), between January and March 2014. The model assessment was performed by the method of weighted values of statistical indicators. The models based on linear measurements as independent variable that provided best performance of LA estimation for T. impetiginosa and T. roseoalba use the average leaflet width (Wla) measurements: LA=10.919×Wla1.854 and LA=6.196×Wla1.684, respectively. For H. chrysotrichus, the model was based on the length and width of leaves (L and W): LA=(0.383×L×W)+16.586. The best models of leaf area estimation considering dry mass (DM) were LA=119.510×DM−32.044×DM2 for H. chrysotrichus, LA=143.610×DM−6.383×DM2 for T. impetiginosa, and LA=90.623×DM for T. roseoalba.